Japanese Pitch Accent Errors by Japanese Students Diponegoro University - Azhar Muhammad Addifa; Muhammad Nur Wahid; Salvia Rifdah (International Journal Labs, 2021)
This study uses a qualitative descriptive method which aims to examine the difficulties experienced by students of the D4 Applied Foreign Language study program in adjusting to the Japanese pitch accent when pronouncing. Of the four language skills, namely listening, speaking, reading and writing, there are difficulties in speaking skills, especially in the pitch accent. Differences in accents can cause feelings of awkwardness and lead to misunderstandings in a conversation because an inappropriate accent can change meaning or definition. So with this we need an appropriate learning method and strategy in practicing Japanese language based on a pitch accent. From the research results, it is known that shadowing can be used in Japanese accent pitch training.